2003
DOI: 10.1086/378401
|View full text |Cite
|
Sign up to set email alerts
|

The DEEP Groth Strip Survey. IX. Evolution of the Fundamental Plane of Field Galaxies

Abstract: Fundamental plane studies provide an excellent means of understanding the evolutionary history of earlytype galaxies. Using the Low Resolution Imaging Spectrograph on the Keck Telescope, we obtained internal stellar kinematic information for 36 field galaxies in the Groth Strip, 21 early-type and 15 disk galaxies. Their redshifts range from 0.3 to 1.0, with a median redshift of 0.8. The slope of the relation shows no difference compared with the local slope. However, there is significant evolution in the zero-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
165
5

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(191 citation statements)
references
References 48 publications
21
165
5
Order By: Relevance
“…3 we present the edge-on projection of the FP in the local (left) and high-redshift samples (right), in addition to the zeropoint and total rms scatter obtained in each case. For our local sample we obtained a zeropoint of c = −9.093, which agrees well with the previous result of Gebhardt et al (2003) (−9.062); and the resulting rms scatter σ tot = 0.113 is not significantly higher than the local value (∼0.1 dex; Fritz et al 2005). However, we found a different FP intercept for the high-redshift galaxies, according to previous studies of FP evolution (for example Gebhardt et al 2003;Fritz et al 2009b).…”
Section: The Fundamental Planesupporting
confidence: 91%
See 3 more Smart Citations
“…3 we present the edge-on projection of the FP in the local (left) and high-redshift samples (right), in addition to the zeropoint and total rms scatter obtained in each case. For our local sample we obtained a zeropoint of c = −9.093, which agrees well with the previous result of Gebhardt et al (2003) (−9.062); and the resulting rms scatter σ tot = 0.113 is not significantly higher than the local value (∼0.1 dex; Fritz et al 2005). However, we found a different FP intercept for the high-redshift galaxies, according to previous studies of FP evolution (for example Gebhardt et al 2003;Fritz et al 2009b).…”
Section: The Fundamental Planesupporting
confidence: 91%
“…In addition, found that the M/L ratios of field galaxies evolves as Δ ln(M/L B ) = (−1.35 ± 0.35)z, similar to cluster galaxies. In contrast, the studies at higher redshift of Treu et al (2002) and Gebhardt et al (2003) found a greater brightening for field galaxies than the one found for cluster galaxies. Restricting the Gebhardt et al (2003) sample to galaxies at z = 0.4, the B luminosities of early-type galaxies would have been ∼0.7 mag brighter than nowadays, which was attributed to a more recent formation epoch of around z = 1.5.…”
Section: Introductioncontrasting
confidence: 68%
See 2 more Smart Citations
“…In the local Universe, red early-type galaxies are the dominant population in rich galaxy clusters, while blue late-type galaxies are the dominant population in the low-density field. Not only galaxy properties, but the formation epoch of galaxies also depends on environment in the sense that cluster galaxies form earlier than field galaxies (e.g., Kuntschner et al 2002;Gebhardt et al 2003;Thomas et al 2005). Earlier studies concentrated on nearby galaxies, but with the recent advent of large telescopes, environment studies at z ∼ 1 became possible.…”
Section: Introductionmentioning
confidence: 99%